Factors Influencing the Occurrence of Female Circumcision in Children in Ladang Bambu Village Medan Tuntungan Subdistrict - Violent Violent; Sopiah Sopiah (MBUnivPress, 2024)
The practice of female circumcision is a tradition that has long been known in society and is recognized by religions in the world such as Judaism, Islam and some Christian followers. Circumcision procedures are usually performed as an act when boys are approaching puberty, but in some regions in Indonesia such as Madura, Java, Sumatra and other regions circumcision is also performed on girls. The purpose of this study was to identify the factors that influence the occurrence of female circumcision in children in Ladang Bambu Village, Medan Tuntungan Subdistrict, 2011. The research design used in this study was descriptive with purposive sampling method with 62 respondents. From the results obtained, the characteristics of respondents showed that the majority were aged 26-30 years (38.7%), the most ethnicity was Javanese, namely 59 respondents (95.2%), and the majority of respondents had a high school education, namely 49 respondents (79.0%). From psychosexual factors that influence the occurrence of female circumcision in children, namely 52 people (84%), sociological factors that influence the occurrence of female circumcision in children, namely 59 people (95.2%), hygiene factors that influence the occurrence of female circumcision in children, namely 58 people (93.5%), myth factors that influence the occurrence of female circumcision in children, namely 55 people (88.7%), religious factors that influence the occurrence of female circumcision in children, namely 62 people (100%). It is expected for health workers to provide education and correct information about traditional practices that develop in the community, especially regarding female circumcision in children.